Semantic Modelling of e-Solutions Using a View Formalism with Conceptual and Logical Extensions - Rajugan, R.; Chang, Elizabeth; Feng, L.; Dillon, Tharam (IEEE, 2005)
In industrial informatics, there exists a requirement to model and design views at a higher level of abstraction. Since the classical view definitions are only available at the query or instance level, modelling and maintaining such views for complex enterprise information systems (EIS) is a challenging task. Further, the introduction of semi-structured data (namely XML) and its rapid adaptation by the commercial and industrial systems increased the complexity for view design and specification. To address such and issue, in this paper we present; (a) a layered view model for XML, (b) a design methodology for such views and (c) some real-world industrial applications of the view model. The XML view formalism is defined at the conceptual level and the design methodology is based on the XML semantic (XSemantic) nets, a high-level object-oriented (OO) modelling language for XML domains.